The formation of onset transients in rooms measured by crosscorrelation - ŻERA, J.; DAROWSKA, M. (Archives of Acoustics, 1994)
A crosscorrelation measure for the degree of change in onset transients caused by reflections in a room was investigated. The measurements were based on a numerically modelled room. It was shown that the variability of the measure depends on the rise time of the source signal and on the delay of the measuring window from the beginning of the sound. The introduced measure is related to the early/late energy parameters of a room, and is associated with a subjective evaluation of the transients.